DIMENSI-DIMENSI SOSIOLOGIS FENOMENA PERNIKAHAN DAN PERCERAIAN DI INDONESIA: DIMENSI-DIMENSI SOSIOLOGIS FENOMENA PERNIKAHAN DAN PERCERAIAN DI INDONESIA - Rozi, Fahrur (Lembaga Marwah Rakyat, 2024)
ABSTRACT Marriage is the completion of half a religion and aims to obtain offspring. Offspring play an important role for parents because they serve as a place for outpouring love and in the future it becomes the hope of parents to always pray for them. However, not all couples want to have children and decide to choose to be childfree (living without children after marriage). In Islam, if the intention is only to delay pregnancy, either by using tools or naturally without terminating the pregnancy from its source, then the law is permissible and this can be an alternative solution for couples who feel they are not ready to have children. Keyword: Phenomenon of Marriage, Divorce, Childfree